Management of rice root-knot nematode, Meloidogyne graminicola in rice (Oryza sativa) - PANKAJ, PANKAJ; SHARMA, H K; SINGH, KHAJAN; LAL, JAGAN (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during kharif season of 2010-12 to study the effect of soil solarization, carbofuran 3G and biocontrol agent Pseudomonas fluorescens on growth of rice (Oryza sativa L.) seedlings and rice root-knot nematode, Meloidogyne graminicola. Combined application of solarization (15 days) either with carbofuran 3G @ 1kg a.i./ha or P. fluorescens @1% WP @ 50g/sq.m, increased the seedling growth up to 30 day after sowing and reduced the number of galls and eggs per egg mass at 24 day after sowing. Therefore, 24 day old seedlings were preferred for transplanting in the main field. We proposed soil application of carbofuran 3G @ 1 kg a.i./ha (3.3 g/m2) before laying nursery. Thus, this intervention was propagated among the farmers of 4 villages (Nekpur, Salempur Jat, Shahpura, Java) with the help of IARI adopted centre (under out reach programme) at Nekpur village, Bulandshahr district of Uttar Pradesh.